Dum (assombrado) complexo de Bartleby: Isto [não] é um livro e eu [não] sou daqui (ou da [im]possibilidade lusófona da Galiza) - Vidal Bouzon, Álvaro J. (Academia Galega da Língua Portuguesa, 2008)
In 2003 the Galizan writer João Guisan published Isto é um livro. Projecto Dicionário Vivo, conceived as ‘a project of a Project’ which would retain an essential relationship with language and writing but would potentially exceed them, crossing the borders of the supposed autonomy of cultural practices and artifacts. What Isto é um livro is articulating are the very conditions of [im]possibility of be[com]ing Lusophone\Lusograph in Spanish Galiza and, in so doing, challenging the nature of the hyphen between the two notions making up the political category of Nation-State.